2015
DOI: 10.1146/annurev-pharmtox-010814-124332
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Hsp90/Hsp70-Based Protein Quality Control for Treatment of Adult Onset Neurodegenerative Diseases

Abstract: Currently available therapies for adult onset neurodegenerative diseases provide symptomatic relief, but are not disease modifying. We explore here a new neuroprotective approach based on drugs targeting chaperone-directed protein quality control. Critical target proteins that unfold and aggregate in these diseases, such as the polylglutamine androgen receptor (spinal and bulbar muscular atrophy), huntingtin (Huntington’s disease), α-synuclein (Parkinson’s disease) and tau (Alzheimer’s disease) are client prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
179
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 138 publications
4
179
0
1
Order By: Relevance
“…As the prevalence of neurodegenerative diseases in the human population ramps up as average life span increases, few effective therapies for these neural diseases, particularly Alzheimer's, have been identified to date despite a large number of clinical trials (Lang 2010;Dunkel et al 2012;Pratt et al 2015). This may be due to the multifactorial nature of neurodegenerative diseases, and targeted inhibition of a single disease pathology may be compensated by concurrent deleterious pathways (Cavalli et al 2008;Lang 2010;Dunkel et al 2012;Huang and Mucke 2012;Sheikh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the prevalence of neurodegenerative diseases in the human population ramps up as average life span increases, few effective therapies for these neural diseases, particularly Alzheimer's, have been identified to date despite a large number of clinical trials (Lang 2010;Dunkel et al 2012;Pratt et al 2015). This may be due to the multifactorial nature of neurodegenerative diseases, and targeted inhibition of a single disease pathology may be compensated by concurrent deleterious pathways (Cavalli et al 2008;Lang 2010;Dunkel et al 2012;Huang and Mucke 2012;Sheikh et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous clinical trials, few effective therapies for neurodegenerative diseases have been identified (Dunkel et al 2012;Pratt et al 2015). This may be due to deficiencies in current animal models to encompass the complexity of the human brain (Lang 2010;t Hart et al 2012;McGonigle and Ruggeri 2014;Sasaki 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock proteins (Hsps) are cellular repair agents that counter the effects of protein misfolding, and their upregulation has been proposed as a potential strategy to counter neurodegenerative disorders (Muchowski and Wacker 2005;Asea and Brown 2008;Pratt et al 2015). The HSPA (Hsp70) family has been widely studied, particularly HSPA1A (Hsp70-1), however HSPA6 (Hsp70B') has received comparatively little attention (Chow and Brown 2007;Noonan et al 2007a;Noonan et al 2007b;Noonan et al 2008a;Noonan et al 2008b;Chow et al 2010;Ramirez et al 2015;Deane and Brown 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, HSPA6 is missing in current animal models of human neurodegenerative diseases. At present, few effective therapies for human neurodegenerative diseases have been identified despite numerous clinical trials (Dunkel et al 2012;Huang and Mucke 2012;Pratt et al 2015). Therapeutic compounds that have been identified and appeared promising in animal models of neurodegenerative Electronic supplementary material The online version of this article (doi:10.1007/s12192-016-0724-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%